Stress triggering of the 2022 Lushan–Maerkang earthquake sequence by historical events and its implication for fault stress evolution in eastern Tibet - Tang, Dawei; Ge, Weipeng; Cao, Xiyu (Frontiers in Earth Science, 2023)
We calculate the Coulomb stress change of the Lushan-Maerkang earthquake sequence on June, 2022, triggered by historical earthquakes since 1900 in eastern Tibet, using the Burgers viscoelastic model. Our results show that: (1) The 1955 M7.6 Kangding and 2008 MW7.9 Wenchuan earthquakes contribute most significant loading effect on the 2022 Lushan earthquake, and the 2013 MW6.6 Lushan earthquake obviously seems to contribute unloading effect on the 2022 Lushan earthquake; (2)The 2021 MW7.3 Maduo earthquake contributes loading effect on the 2022 Lushan earthquake, but the 2022 Lushan earthquake triggers the MW5.6 Maerkang earthquake on June 10, 2022, and the flowing events, including the MW5.9 Maerkang, and MW4.9 Maerkang earthquakes. (3) Relaxation influence of a viscoelastic medium in lower crust plays a significant role in earthquake preparation, while a fault in the late earthquake cycle might be ruptured by slim stress disturbance near a stress positive and negative conversion cross-border from a far-field earthquake.